If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1(x + -11) = 8(x + 7) Reorder the terms: 10 + -1(-11 + x) = 8(x + 7) 10 + (-11 * -1 + x * -1) = 8(x + 7) 10 + (11 + -1x) = 8(x + 7) Combine like terms: 10 + 11 = 21 21 + -1x = 8(x + 7) Reorder the terms: 21 + -1x = 8(7 + x) 21 + -1x = (7 * 8 + x * 8) 21 + -1x = (56 + 8x) Solving 21 + -1x = 56 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 21 + -1x + -8x = 56 + 8x + -8x Combine like terms: -1x + -8x = -9x 21 + -9x = 56 + 8x + -8x Combine like terms: 8x + -8x = 0 21 + -9x = 56 + 0 21 + -9x = 56 Add '-21' to each side of the equation. 21 + -21 + -9x = 56 + -21 Combine like terms: 21 + -21 = 0 0 + -9x = 56 + -21 -9x = 56 + -21 Combine like terms: 56 + -21 = 35 -9x = 35 Divide each side by '-9'. x = -3.888888889 Simplifying x = -3.888888889
| 2ln(2x+4)=30 | | 6/17p=-12/7 | | -5/3k15 | | 4y^4-4y^2+1=0 | | r(2r)/3r | | 7t^2-13t+8=0 | | 1/3/12.50 | | 5m+10n+15c= | | 0.35(8g-3)=0.05(9g-5) | | 7x-23/4=-4 | | -2x+6y-4z=32 | | (5x2-6x)/3x | | (-2x+6)=(5x-2y) | | (5x-6x)/3x | | 2x-3y+8z=16 | | log(3)(5x-4)=1 | | X^2=64/225 | | 8x+25=12x-31 | | -15/-3= | | 4x^2+4y^2-32x-64=0 | | 10k-4=2k-12 | | -3/-5= | | 3x(4y+12)=2y | | 8(x-9)=-2(x-41) | | -6(x-6)=3(x-9) | | x=-55+5x | | 6(2/3)-2= | | g(-4)=2x-3x | | 8m+6n+2m-1n=0 | | 4(x-5)/-2= | | A-43/8=21/2 | | 12-5x=10-3x |